Anaesthesia Management of Patient at 16 Weeks Pregnancy with Primary Malignant Bone Tumour Underwent Hemipelvectomy Surgery - Sinardja, Cynthia Dewi; Senapathi, Tjokorda Gde Agung; Suarjaya, I Putu Pramana; Suranadi, I Wayan; Kusuma, Oscar Indra; D.H., Asterina (Bali Journal of Anesthesiology, 2018)
Chondrosarcoma is a type of sarcoma that affects the bones and joints. It is a rare cancer that accounts for about 20% of bone tumours and is diagnosed in approximately 600 patients each year in the United States. Chondrosarcoma typically affects adults between the age of 20 and 60 years old. The disease usually starts in the bones of the arms, legs or pelvis, but it can be found in any part of the body that contains cartilage. Sometimes chondrosarcoma grows on an otherwise healthy bone or it grows on a benign bone tumour (an enchondroma or osteochondroma). Non-obstetric surgery during pregnancy is not uncommon and can have excellent outcomes with proper planning. Between 0.75% and 2% of pregnant women require non-obstetric surgery. Surgery can be required during any stage of pregnancy depending on the urgency of the indication. When caring for pregnant women undergoing non-obstetric surgery, safe anaesthesia must be provided for both the mother and the child. Thorough understanding of the physiological and pharmacological adaptations to pregnancy is required to ensure maternal safety. Fetal safety requires avoidance of potentially dangerous drugs at critical times during fetal development, assurance of continuation of adequate uteroplacental perfusion, and avoidance and/or treatment of preterm labour and delivery.Pregnant patients beyond 18â20 weeks of gestation should be positioned with a 15Â° left lateral tilt, to reduce aortocaval compression and supine hypotension syndrome. Regional anaesthesia with combined spinal epidural is an option for this case. Regional anaesthesia does reduce the exposure of foetus to potential teratogens, avoids the potential risk of failed intubation and aspiration, and provides excellent post-operative analgesia. The major concern with neuraxial anaesthesia is maternal hypotension, which may reduce placental perfusion. Â During anaesthesia and surgery, foetal well-being is best ensured by careful maintenance of stable maternal haemodynamic parameters and oxygenation. Close monitoring of foetal responses for signs of distress is strongly advocated.